2007
DOI: 10.1677/erc-06-0091
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin signals in prostate cancer cells through Akt to activate the mammalian target of rapamycin pathway

Abstract: Adiponectin has received much attention due to its beneficial effects on insulin sensitivity, and epidemiologic studies have further shown an inverse association between adiponectin levels and risk for multiple tumors, which is independent of the IGF system or other risk factors. Previous studies have shown that adiponectin can activate AMP-activated protein kinase (AMPK) in myocytes, hepatocytes, and adipocytes, suggesting that adiponectin may suppress tumor development through AMPK activation and subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 66 publications
2
39
1
Order By: Relevance
“…Our observations are consistent with the expected consequences of AMPK activation, whereas the mechanism underlying the activation of mTOR observed by others remains unclear (26). Furthermore, we observed growth inhibition by adiponectin under our experimental conditions, whereas effects on growth were not reported in the study that used higher adiponectin concentrations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our observations are consistent with the expected consequences of AMPK activation, whereas the mechanism underlying the activation of mTOR observed by others remains unclear (26). Furthermore, we observed growth inhibition by adiponectin under our experimental conditions, whereas effects on growth were not reported in the study that used higher adiponectin concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to our observations, a recent study reported unexpected activation of mTOR and S6K in prostate cancer cells exposed to adiponectin (26). The difference in results may be related to important differences in experimental conditions: We used adiponectin at physiologic concentrations, Twenty-four hours after transfection, cells were treated with adiponectin (500 ng/mL) for 72 h. Cell proliferation in each well was measured by Alamar Blue dye reduction.…”
Section: Discussioncontrasting
confidence: 91%
“…Regarding cancer cells, we reported that adiponectin decreased cell proliferation in colorectal cancer cells through activation of AMPK and inhibition of mTOR and consecutive molecules [6]. On the other hand, Barb et al reported that adiponectin activated AMPK but did not inhibit mTOR in prostate cancer cells [85]. Because the effect of adiponectin on the mTOR signaling pathway may be cancer cell type specific, more detailed studies of the role of adiponectin in cancer cells are needed.…”
Section: Adiponectin Mediates Mtor/s6k Signaling Pathway In Cancermentioning
confidence: 99%
“…Specifically, activation of inflammatory signaling pathways such as NF-kB and c-Jun N-terminal kinase 1, along with increased IL-1β, TNF and IL-6 have been linked with tumorigenesis [45][46][47]. Second, adipocyte-secreted adiponectin has the potential to influence tumor growth by affecting the mTOR and AMP-activated protein kinase pathways [48,49].…”
mentioning
confidence: 99%